SEMIOTIC INTERPRETATION OF COLOR IN JAVANESE TEDAK SITEN CEREMONY TEXT - VANIA DWISARIKA RISKIA; ZAINUDDIN ZA; SYAMSUL BAHRI (LINGUISTICA, 2022)
The purpose of this study was to find the true meaning of color used in Tedak Siten Javanese ceremony text. The study was conducted by using desccriptive method. The data of the study were photos, video and also interview section with the informans. The data analysis were taken by observing, interviewing and listing the data into some classification. The data were analyzed based on the theory that proposed by Charles Saunders Pierce’s Semiotic Triangle and Rolland Barthes. The findings identify that there were seven kinds of color which used in Tedak Siten, they were black, purple, blue, green, red, yellow, and whiter. There are no rules for the colors arrangement. According to both of theories black symbolized equality, purple symbolized wealth, blue symbolized trustworthy, green symbolized lucky, red symbolized love, yellow symbolized happy and white symbolized pure.